PENERAPAN METODE SIMAAN DALAM MENINGKATKAN HAFALAN AL-QUR’AN DI PONPES AR-RAUDHOH KASOMALANG - NURSEHA, AFIF (PT. Banjarese Pacific Indonesia, 2023)
The simaan method is the activity of performing the memorization of the Qur'an with bilghaib to the listeners of either one or more people. This research was conducted with the aim of knowing the Application of the Simaan Method in Improving the Memorization of the Qur'an at the Ar-Raudhoh Islamic Boarding School. The method used in this study is a descriptive qualitative approach method, by describing or describing the results of the research carried out such as interviews, observations and documentation. The population in this study is all students and teachers in the Ar-raudhoh Islamic boarding school. while the sample in this study was a total of 5 informants who were believed to have the information needed and could represent from the population. The results of this study are 1) preparation for the implementation of simaan at the Ar-raudhoh Islamic boarding school, namely by repeating memorization as often as possible and for a long time. 2) the implementation of the simaan method in the Ar-raudhoh islamic boarding school is a.simaan weekly, b.simaan semester, c.simaan memorization even 5, 10,15, 20, 25 juz, d.simaan kubro is simaan 30 juz in one sitting. 3) the simaan method can improve the memorization of the Qur'an in the Ar-raudhoh islamic boarding school by careful and continuous preparation, but if the simaan method is not done with istiqomah, then memorization will not be maintained. 4) Tahsin can improve the memorization of the Qur'an in terms of minimizing mistakes, because in Tahsin reading the Qur'an must be done carefully, because if ignored it will cause a change in meaning. 5) driving factors in carrying out simaan methods such as: giving motivation, giving memorization targets, desires from oneself and others. The inhibiting factors include: insecurity, fear, poor preparation, many mistakes, many similar verses.